Integral field 3D spectroscopy: Techniques and prospects - Thatte, N; Eisenhauer, F; Tecza, M; Mengel, S; Genzel, R; Monnet, G; Bonaccini, D (1999)
The technique of integral field spectroscopy,: which provides simultaneous spectra for each pixel of a contiguous two-dimensional field of view, holds tremendous promise for improving our ability to study circumstellar environments. The technique becomes especially important at near infrared wavelengths, where rapid changes in the night sky background level limit the use of standard scanning techniques. In addition, combining the capabilities of adaptive optics systems with near infrared integral field spectrographs provides an unique way to enhance-spatial resolution for ground based observations. We present the technique of integral field spectroscopy, with special emphasis on the near infrared, and illustrate future developments by describing SINFONI, an adaptive optics assisted near infrared integral field spectrometer for the ESO VLT.